Precision agriculture technology for determination of underground water resources / Muhammad Hamizan Nordin - Nordin, Muhammad Hamizan (Faculty of Plantation and Agrotechnology, 2018)
Water is one of the important component in our daily life. The need for water has increasing every day and has universal function, which is not only for drinking but also for any usefulness. For agricultural activity, water are one of the main components for daily use in the field. Sometimes there will be a drought season that will decrease the water availability that will cause declining on water requirement for plants. Thus, the requirement for underground water is important to fill the necessity of water planting. The study were conducted at UiTM Jasin’s Farm and the data were taken from Google Earth Pro before transfer into ArcMap to get the lowest altitude in the project area. Garmin eTrex Legend HCx were specifically used in this research, which the function is to locate the coordinates of the lowest elevation in research area. Then, the area were analyzed to know the nature of the area can be proof that lowest altitude of an area can access underground water with consuming less time. From the result, this method have reduce the time to access the underground water. In conclusion, the most dominant factors is the lowest altitude of the area to get the into the underground water. For recommendation, this research can be continued by obtain elements contained in groundwater UiTM Jasin’s Farm based on this research.